Preparation and properties of metallocene ethylene copolymer crosslinked by vinyltrimethoxysilane - Kalyanee Sirisinha (2018)
Silane-grafting and water-crosslinking of ethylene-octene copolymer (EOR) was carried out. The influences of grafting formulation, comonomer content in EOR and time of the crosslinking process on grafting efficiency, degree and rate of crosslinking were investigated. The mechanical properties of various crosslinked samples are reported together with correlations with their gel contents. The results show that the extent of grafting increased with an increase in the amounts of dicumyl peroxide (DCP) and vinyltrimethoxysilane (VTMS) used in the reaction. The degree of crosslinking depended mainly on the extent of grafting, while the rate of the crosslinking process depended on the amount of amorphous phase in the samples. In this study, the variation of gel contents in the samples (0-77 %) had no significant influence on tensile properties. A large number of uncrosslinked regions are believed to exist inhomogeneously within the crosslinked polymers even after the sample has reached maximum gel content. The content of gel did not increase further when the crosslinking time was increased beyond that of reaching maximum gel, but the polymer network became denser, resulting in changes in polymer behaviour. © 2005 Society of Chemical Industry.